(3G(B{u(3FEDF(B}{u(3FECC(B}(3hG(B{u(3FEE4(B}(3d G(B{u(3FEDF(B}{u(3FEE4(B}(3D(B{u(3FE9C(B}(3QI (B{u(3FECB(B}{u(3FEE0(B}{u(3FEF0(B} (3EOQGc G(B{u(3FEDF(B}{u(3FECC(B}{u(3FEE4(B}{u(3FEFC(B}(3A (B{u(3FEDF(B}{u(3FEE0(B}{u(3FE9C(B}{u(3FED8(B}{u(3FE94(B} {u(3FED3(B}{u(3FEF0(B} (3G(B{u(3FEDF(B}{u(3FEE4(B}{u(3FE8E(B}(3Q(B{u(3FEDB(B}{u(3FE94(B} (3G(B{u(3FEDF(B}{u(3FE98(B}{u(3FEA0(B}{u(3FE8E(B}(3Q(B{u(3FBFF(B}{u(3FE94(B} : s (3OQG(B{u(3FEB4(B}{u(3FE94(B} {u(3FE98(B}(3W(B{u(3FE92(B}{u(3FBFF(B}{u(3FED8(B}{u(3FBFF(B}{u(3FE94(B} {u(3FEDF(B}{u(3FEE0(B}{u(3FEE4(B}(3hG(B{u(3FED7(B}{u(3FECA(B} (3GdE(B{u(3FEDF(B}{u(3FEDB(B}{u(3FE98(B}(3Qh(B{u(3FEE8(B}{u(3FBFF(B}{u(3FE94(B} / s - (3cQje jMji eMeO Ndjds; (3YHjQ YHOGdQMef eMQhS (B: s ((3GdbGgQI (B: s (3cQje jMji eMeO Ndjd (B: s, 2015)
(3jgOa GdHMK Edi OQGSI GdYhGed GdeDKQI Ydi KbI GdeSJgdc h HNGUI GdeSJgdcjf GdeJYGedjf eY GdehGbY GdGdcJQhfjI aj GSJjaGA WdHGJge h TQGA GMJjGLGJge GdeNJdaI h gd JJCKQ GdKbI HGdNUGFU GdOjehLQGajI GdeJYOOI dTQGFM GdeSJgdcjf GdeNJdaI (B. (3dJMbjb gPG GdgOa (B: (3GYJeO GdHMK Ydi eQGLYI GdOQGSGJ GdSGHbI h JMdjd GdHjGfGJ GdKGfhjI h GdOQGSI GdGSJWdGYjI ai JMOjO eTcdI GdHMK h ENJjGQ eJZjQGJ GdHMK h UjGZI GdaQhV h dbO JhUd GdHMK Edi Efg jhLO JCKjQ eYfhj EjLGHj Hjf eSJhi GdCeGf ddehbY GdGdcJQhfj h eSJhi GOQGc KbI GdeTJQjjf ajg ceG Efg jhLO JCKjQ eYfhj EjLGHj Hjf MeGjI GdeYdheGJ GdTNUjI ddeSJNOe h eSJhi GdKbI aj GdehbY GdGdcJQhfjs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJLGQI (B- (3bSe EOGQI GdCYeGds
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJShjb YHQ GdGfJQfJs; (3GdKbI aj GdeGQcI GdJLGQjI ddehbY GdGdcJQhfjs; (3GdehGbY GdGdcJQhfjI GdJLGQjIs